Genetic insights into the modification of the pre-fertilization mechanisms during plant domestication. (1st June 2019) - Manrique, Silvia; Friel, James; Gramazio, Pietro; Hasing, Tomas; Ezquer, Ignacio; Bombarely, Aureliano
Abstract : Domestication often aims to modify plant reproductive mechanisms. This article reviews traits and genes involved in pre-fertilization stages of plant reproduction that have been modified during domestication. Abstract: Plant domestication is the process of adapting plants to human use by selecting specific traits. The selection process often involves the modification of some components of the plant reproductive mechanisms. Allelic variants of genes associated with flowering time, vernalization, and the circadian clock are responsible for the adaptation of crops, such as rice, maize, barley, wheat, and tomato, to non-native latitudes. Modifications in the plant architecture and branching have been selected for higher yields and easier harvests. These phenotypes are often produced by alterations in the regulation of the transition of shoot apical meristems to inflorescences, and then to floral meristems. Floral homeotic mutants are responsible for popular double-flower phenotypes in Japanese cherries, roses, camellias, and lilies. The rise of peloric flowers in ornamentals such as snapdragon and florists' gloxinia is associated with non-functional alleles that control the relative expansion of lateral and ventral petals. Mechanisms to force outcrossing such as self-incompatibility have been removed in some tree crops cultivars such as almonds and peaches. In this review, we revisit some of these important concepts from the plant domestication perspective, focusing on four topics related to the pre-fertilization mechanisms: flowering time, inflorescence architecture, flower development, and pre-fertilization self-incompatibility mechanisms.